A novel hydroxyapatite composite reinforced with titanium nanotubes coated on Co–Cr-based alloy. (December 2015) - Rezazadeh Shirdar, Mostafa; Sudin, Izman; Taheri, Mohammad Mahdi; Keyvanfar, Ali; Yusop, Mohd Zamri Mohd; kadir, Mohammed Rafiq Abdul
Abstract: In this study, hydroxyapatite (HA) and TiO2 nanotubes (TNT) were synthesized using sol–gel and Rapid Breakdown Adonization (RBA) methods respectively. Three different ratios of HA-TNT mixture were prepared to be coated on the Co–Cr-based alloy via dip coating technique. The synthesized TNT and composite coated samples were characterized using X-ray diffraction (XRD), Field Emission Scanning Electron Microscope (FESEM), and Transmission Electron Microscopy (TEM). Electrochemical corrosion behavior of the coated samples were evaluated in SBF solution and compared to bare specimen and HA coated sample. In addition, the mechanical properties of the composite layer including Vickers micro-hardness and bonding strength were examined. The HA-TNT coating layer shows uniform and compact surface morphology with the thickness of about 86–94 μm. Results indicate that the HA-TNT composite can provide higher mechanical properties and corrosion resistance as compared to the HA coated sample. The immersion test reveals that the Cr ion release from coated substrate reduced over 21 days. The composite layer with highest ratio of TNT presents the best mechanical and electrochemical properties. The findings indicate that the overall performance of the proposed composite layer is very encouraging and it can be an alternative to the current HA coated layer for orthopedic implants. Highlights: TiO2 with nanotubes structure was utilized in hydroxyapatite composite. The HA/TiO2 Composite were coated on Co–Cr–Mo Alloy. Mechanical and electrochemical properties of novel coated composite was improved.